Robust synthesis of NIR-emissive P-rhodamine fluorophores. Issue 8 (10th February 2020) - Sauer, Maria; Nasufovic, Veselin; Arndt, Hans-Dieter; Vilotijevic, Ivan
Abstract : A library of P-rhodamines was prepared via a new robust sequence that creates the core heterocycle by addition of diaryllithium reagents to esters. The first SAR study for P-rhodamines shows that they are NIR-emissive and highly bright fluorophores. Abstract : P-Rhodamines were accessed by implementing a robust three step sequence consisting of (i) addition of m -metallated anilines to dichlorophosphine oxides, (ii) selective dibromination, and (iii) cyclization of the diaryllithium reagents derived from the dibromides to form the dihydroacridophosphine core of P-rhodamines. A modified route was developed to produce non-symmetric P-rhodamines. A library of prepared P-rhodamines provides first insight into dependence of fluorophore properties on the structure of P-rhodamines. A P-rhodamine with highest batochromic shifts and quantum yields in the class was identified.